Subclinical hypothyroidism and clinical outcomes after cardiac surgery: A systematic review and meta-analysisCentral MessagePerspective - Michele Dell’Aquila, BS; Camilla S. Rossi, MD; Tulio Caldonazo, MD; Gianmarco Cancelli, MD; Lamia Harik, MD; Giovanni J. Soletti, MD; Kevin R. An, MD; Jordan Leith, BS; Hristo Kirov, MD; Mudathir Ibrahim, MD; Michelle Demetres, MLIS; Arnaldo Dimagli, MD; et al. (JTCVS Open, 2024)
Background: Subclinical hypothyroidism (SCH) is associated with major adverse cardiovascular events. Despite the recognized negative impact of SCH on cardiovascular health, research on cardiac postoperative outcomes with SCH has yielded conflicting results, and patients are not currently treated for SCH before cardiac surgery procedures. Methods: We performed a study-level meta-analysis on the impact of SCH on patients undergoing nonurgent cardiac surgery, including coronary artery bypass grafting and valve and aortic surgery. The primary outcome was operative mortality. Secondary outcomes were hospital length of stay (LOS), intensive care unit (ICU) stay, postoperative atrial fibrillation (POAF), intra-aortic balloon pump (IABP) use, renal complications, and long-term all-cause mortality. Results: Seven observational studies, with a total of 3445 patients, including 851 [24.7%] diagnosed with SCH and 2594 [75.3%] euthyroid patients) were identified. Compared to euthyroid patients, the patients with SCH had higher rates of operative mortality (odds ratio [OR], 2.57; 95% confidence interval [CI], 1.09-6.04; P = .03), prolonged hospital LOS (standardized mean difference, 0.32; 95% CI, 0.02-0.62; P = .04), a higher rate of renal complications (OR, 2.53; 95% CI, 1.74-3.69; P < .0001), but no significant differences in ICU stay, POAF, or IABP use. At mean follow-up of 49.3 months, the presence of SCH was associated with a higher rate of all-cause mortality (incidence rate ratio, 1.82; 95% CI, 1.18-2.83; P = .02). Conclusions: Patients with SCH have higher operative mortality, prolonged hospital LOS, and increased renal complications after cardiac surgery. Achieving and maintaining a euthyroid state prior to and after cardiac surgery procedures might improve outcomes in these patients.